1996
DOI: 10.1093/chemse/21.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Taste Perception Following Mental or Physical Stress

Abstract: Taste perception depends not only on the chemical and physical properties of tastants, but may also depend on the physiological and psychological conditions of those who do the tasting. In this study, the effects of mood state on taste sensitivity was evaluated in humans who were exposed to conditions of mental or physical fatigue and tension. Taste responses to quinine sulfate (bitter), citric acid (sour) and sucrose (sweet) were tested. The intensity of the taste sensations were recorded by a computerized ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
3
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 9 publications
6
67
3
2
Order By: Relevance
“…It has been reported that the vigor score is negatively correlated with the fatigue score (8,9). Furthermore, it has been reported that the vigor score decreased and the fatigue score increased during both physical (14) and mental workloads (11). These previous observations suggest that the vigor score is closely related to fatigue.…”
Section: Discussionmentioning
confidence: 80%
“…It has been reported that the vigor score is negatively correlated with the fatigue score (8,9). Furthermore, it has been reported that the vigor score decreased and the fatigue score increased during both physical (14) and mental workloads (11). These previous observations suggest that the vigor score is closely related to fatigue.…”
Section: Discussionmentioning
confidence: 80%
“…The relationship between fatigue and taste palatability has been investigated by Nakagawa et al (1996), who evaluated the effect of mood on taste sensitivity. Following the induction of mental stress, the perceived duration of bitter, sour, and sweet taste sensations was shortened in the induced group compared to that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…There was, nevertheless, no significant difference between bitter and sweet sensations following physical stress. However, the duration of the aftertaste of sourness was significantly increased (Nakagawa et al, 1996). Horio and Kawamura (1998) examined the change in palatability and threshold of various taste solutions after the induction of exercise stress.…”
Section: Discussionmentioning
confidence: 99%
“…The second group consists of factors with systemic origin, i.e., low zinc concentrations [16,27], hormone disturbances [10], head trauma, viral infections, irradiation [7], and adverse effect of medication [1,31]. The third group is comprised of psychological factors such as depression [8,20,21] and stress [22].…”
Section: Introductionmentioning
confidence: 99%